1991
DOI: 10.2527/1991.69104137x
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake, rectal temperature, and serum mineral concentrations of feedlot cattle fed zinc oxide or zinc methionine and challenged with infectious bovine rhinotracheitis virus4

Abstract: Three experiments were conducted using feedlot steers in a randomized block design to determine the effect of zinc methionine (ZnMet) and zinc oxide (Exp. 3) on feed intake (DMI), rectal temperature, and serum mineral concentrations of feedlot cattle challenged with infectious bovine rhinotracheitis virus (IBRV). All the steers used were seronegative to IBRV. Steers were adapted for 7 d to their respective diets and challenged with 3.7 x 10(5) plaque forming units of IRBV on d 0 of each experiment. Live BW, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 3 publications
5
42
0
2
Order By: Relevance
“…Moreover, if this complex is complemented with Mn-, and Cu-specific aminoacids complexes and cobalt glucoheptonate, further improvement of milk production, reproductive performance and claw integrity is observed (Nocek et al, 2000;Bicalho et al, 2007). Several studies have also reported improvements in reproductive performance, immune response and hoof health in ruminants supplemented with these minerals (Hutcheson, 1990;Chirase et al, 1991;Graham, 1991;Campbell et al, 1999;Nocek et al, 2000;Lucy, 2001;Margerison et al, 2002) but we have not found reports on how this supplementation may affect the plasma concentrations of metabolites and metabolic hormones. Moreover, the experimental designs have been performed under stabulation conditions with controlled nutritional schemes and less is known about its repercussions under grazing conditions.…”
mentioning
confidence: 72%
“…Moreover, if this complex is complemented with Mn-, and Cu-specific aminoacids complexes and cobalt glucoheptonate, further improvement of milk production, reproductive performance and claw integrity is observed (Nocek et al, 2000;Bicalho et al, 2007). Several studies have also reported improvements in reproductive performance, immune response and hoof health in ruminants supplemented with these minerals (Hutcheson, 1990;Chirase et al, 1991;Graham, 1991;Campbell et al, 1999;Nocek et al, 2000;Lucy, 2001;Margerison et al, 2002) but we have not found reports on how this supplementation may affect the plasma concentrations of metabolites and metabolic hormones. Moreover, the experimental designs have been performed under stabulation conditions with controlled nutritional schemes and less is known about its repercussions under grazing conditions.…”
mentioning
confidence: 72%
“…Supplementation of Zn methionine to a basal diet containing more than 25 mg Zn/kg DM had no effect on feed intake ewes. Feed intake was not significantly affected by Zn source or level during the experiment [24]. The feed intake tended to drop less in zinc methionine fed calves challenged with infectious Bovine Rhinotracheits (IBR) compared to ZnO fed calves.…”
Section: Digestibility Coefficients Nutritive Values and Nitrogen Utmentioning
confidence: 85%
“…Gershwin and colleagues (1985) reported that zinc plays an indispensable role in the development and maintenance of immunocompetence. Zinc supplementation enhanced the recovery rate of cattle su¡ering from infectious bovine rhinotrachitis virus (Chirase et al, 1991). Zinc is an important factor/cofactor in various metabolic pathways, and a decrease in AST and ALT levels was observed in zinc-de¢cient cattle.…”
Section: Discussionmentioning
confidence: 98%